Pengaruh Persepsi Kemanfaatan, Risiko, Efektifitas Terhadap Minat Menggunakan Fintech Sebagai Alat Pembayaran Pada Cafe dan Resto di Kota Solok - Larasati Rahmadani; Rita Dwi Putri; Siska Yulia Defitri (Politeknik Raflesia Press, 2025)
The Adoption of financial technology (fintech) in cafes and restaurants is very important to increase operational efficiency. This research aims to examine the influence of perceptions of usefulness, risk and effectiveness on interest in using fintech as a means of payment. With a quantitative approach, data was collected from 124 respondents through a structured survey and analyzed using Partial Least Squares (SmartPLS 3.0). The research results show that perceptions of usefulness, risk, and effectiveness significantly influence interest in using fintech. These results have practical implications for small businesses and policy makers to encourage the adoption of digital payments in local economies.